'Constrained flexibility' as a tool to facilitate reform of the EU budget - Buti, Marco; Nava, Mario; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium : European Comission : Directorate-General for Economic and Financial Affairs, 2008)
Some researchers have recently introduced productive government investment spending into Dynamic stochastic general equilibrium (DSGE) models, adding a supply channel. This paper takes a similar perspective but it also introduces the government consumption good into the household utility function and this consumption good is supplied by a government production function. While higher government investment can increase private output and household consumption in the future, in the short run household utility is likely to decline because current consumption of private and government goods is shifted into investment and the supply of privately produced consumption goods is reduced. These considerations are especially relevant for euro-area members because fiscal policy is their only national macroeconomic policy tool.
Economic Papers.